HIF-1 signalling pathway was identified as a potential new pathway for Icariin’s treatment against Alzheimer’s disease based on preclinical evidence and bioinformatics - You, Mingyao; Yuan, Ping; Li, Liangqian; Xu, Hongbei (Frontiers in Pharmacology, 2022)
Aim: Alzheimer's disease (AD) is a neurodegenerative condition that is characterized by the gradual loss of memory and cognitive function. Icariin, which is a natural chemical isolated from Epimedii herba, has been shown to protect against AD. This research examined the potential mechanisms of Icariin’s treatment against AD via a comprehensive review of relevant preclinical studies coupled with network pharmacology. Methods: The PubMed, Web of Science, CNKI, WANFANG, and VIP databases were used to identify the relevant studies. The pharmacological characteristics of Icariin were determined using the SwissADME and TCMSP databases. The overlapping targets of Icariin and AD were then utilized to conduct disease oncology (DO) analysis to identify possible hub targets of Icariin in the treatment of AD. The hub targets were then used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses, and the interactions of the targets and Icariin were assessed via molecular docking and molecular dynamics simulation (MDS). Results: According to the literature review, Icariin alleviates cognitive impairment by regulating the expression of Aβ1-42, Aβ1-40, BACE1, tau, hyperphosphorylated tau, and inflammatory mediators. DO analysis revealed 35 AD-related hub targets, and the HIF-1 signalling pathway was ranked first according to the KEGG pathway analysis. Icariin effectively docked with the 35 hub targets and HIF-1α, and the dynamic binding of the HIF-1-Icariin complex within 100 ns indicated that Icariin contributed to the stability of HIF-1α. Conclusion: In conclusion, our research used a literature review and network pharmacology methods to identify the HIF-1 signalling pathway as a potential pathway for Icariin’s treatment against AD.